Assessing the impact of future altimeter constellations in the Met Office global ocean forecasting system - R. R. King; M. J. Martin; L. Gaultier; J. Waters; C. Ubelmann; C. Donlon (Ocean Science)
Satellite altimeter measurements of sea surface height (SSH) are a crucial component of current operational ocean forecasting systems. The launch of the Surface Water and Ocean Topography (SWOT) wide-swath altimeter (WiSA) mission is bringing a step change in our observing capacity with 2D mesoscale structures now able to be observed over the global ocean. Proposals are now being considered for the make-up of the future altimeter constellation. In this study we use Observing System Simulation Experiments (OSSEs) to compare the impact of additional altimeter observations from two proposed future satellite constellations. We focus on the expected impact on the Met Office operational ocean analysis and forecasting system of assimilating an observation network including either 12 nadir altimeters or 2 wide-swath altimeters.